A shepherd looks at Psalm 23 - Keller, W. Phillip (Weldon Phillip), 1920-1997. (Grand Rapids, Mich. : Zondervan, 2007)
With over 2 million copies sold, Phillip Keller's beloved contemporary classic spans the decades with its uplifting insights on Psalm 23. Pairing Keller's sublime reflections with the New International Version, this edition sheds light for a new generation of readers on the nature and ways of sheep--and of the Good Shepherd who cares for them.
Keywords: Bible. -- Meditations